Iridium half-sandwich complexes with di- and tridentate bis(pyridylimino)isoindolato ligands: stoichiometric and catalytic reactivity - Müller, Astrid; Bleith, Tim Manuel; Roth, Torsten; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2015)
A series of κ2-(N,N)-coordinated bis(2-pyridylimino)isoindolato (BPI) complexes [Cp*Ir(BPI)Cl], which possess “three-legged piano-stool” structures, with the iridium atom being coordinated by the Cp* ligand 2 × N and Cl, were prepared via deprotonation of the BPIH ligands with either potassium hydride or LDA and subsequent reaction with [Cp*IrCl2]2 in THF. Cationic complexes [Cp*Ir(BPI)]+ containing κ3-(N,N,N)-coordinated BPI ligands were prepared as well as complexes with bidentate-coordinated BPI ligands, where the chloride ligand was substituted by either neutral or anionic ligands. Substitution in the ortho-position of the PBI ligands led to the formation of cycloiridated κ3-(N,N,C) species. Upon substitution of the anionic ligand by triphenylphosphine, a product was obtained with a hitherto unobserved κ2-(N,N) coordination of oMe-BPI to the metal center via the deprotonated nitrogen atom of the isoindole unit and one of the imine nitrogen atoms of the BPI ligand. A series of (para-cymene) osmium half-sandwich complexes with analogous structures and reactivities to their isoelectronic Cp*Ir(BPI) congeners were also prepared. Finally, it has been demonstrated that both Ir and Os complexes are catalytically active in the transfer hydrogenation of various ketones and imines.